Quality assessment of smoked Clarias gariepinus from farms and markets in Ibadan, Nigeria: implications for public health - Oluwafemi Olowojuni; Nana Kadidia Traore; Flora Eyibio Olaifa (Acta Aquatica: Aquatic Sciences Journal, 2026)
Smoked fish is widely consumed in Nigeria and may serve as a route of exposure to microbial contamination and toxic metals. This study assessed microbial quality, spoilage indicators, proximate composition, and heavy metal content associated with smoked Clarias gariepinus obtained from two farms (A and B) and two markets (A and B) in Ibadan, Nigeria, with implications for public health. Spoilage indicators were higher in market-sourced samples, with peroxide values ranging from 0.93 ± 0.40 mEq/kg in Farm B to 3.37 ± 0.29 mEq/kg in Market B. Total volatile base nitrogen and thiobarbituric acid values were also elevated, indicating increased lipid oxidation and protein degradation. Total viable (3.68 ± 0.79) × 10⁴ and fungal counts (2.66 ± 0.54) × 10⁵ were higher in market samples, although coliforms were not detected. Microbial profiling revealed greater diversity in market fish, including Pseudomonas, Aspergillus, Saccharomyces, and Geotrichum. Proximate composition was comparable across sources, with low moisture content (4.70–6.70%) and water activity (0.850–0.910), reflecting effective drying. Heavy metal concentrations were generally low in farmed fish but higher in market samples, particularly Market B, following the order arsenic > chromium > lead > cadmium, while mercury was not detected. Estimated daily intake and target hazard quotient values were below established safety thresholds, indicating no health risk. However, elevated spoilage indices and metal levels in market fish highlight the need for routine monitoring to protect consumer health. Keywords: Biochemical Spoilage; Fish; Markets; Microbial Quality